Epistemological rupture with modernity: the case of citizenship - Rivera Cubillos, Daniela Fernanda (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The objective of this article is to present a diagnosis of the change of era for social theory, considering the case of the notion of citizenship and its relationship to the development of modern States; through a foundation in favour of an epistemological break with Modernity, which makes it possible to identify and understand that said concept, based on a review and reconceptualization from a social reality located and interrelated from Latin America, can no longer be seen in a reductionist way, but rethought –and valued– in all its dimensions (Pelfini, 2007), which has not only enabled the transformation of these modern societies (Montesinos, 2004), but also enables a rethinking of the relationship between the State and society, where they have emerged. initiatives of different sign and modality in the region in this field (Castro, 2014).